المجربات في تفاسير القرآن الكريم - Adjdir, Nasreddin; El Mahdi, Boudaoued Mohammed (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2023)
This study aims to indicate the name of the experiments so that a person in his life likes to bring righteousness to him as a shepherd for the instinct that broke them, and the mental laws that do not favor anyone indicate attachment to those returns that overflow it with good, from this point of view people stick to experiments that benefit them, but the latter is limited by several legal caveats, especially concerning the corruption of belief or dragged into a greater spoiler, so this study came to look for the extent to which the people of interpretation of the experiments and seize Reliable controls in working out